Counting abelian extensions by Artin–Schreier conductor - Gundlach, Fabian (Proceedings of the American Mathematical Society)
Let G G be a finite abelian p p -group. We count étale G G -extensions of global rational function fields F q ( T ) \mathbb F_q(T) of characteristic p p by the degree of what we call their Artin–Schreier conductor. The corresponding (ordinary) generating function turns out to be rational. This gives an exact answer to the counting problem, and seems to beg for a geometric interpretation. This is in contrast with the generating functions for the ordinary conductor (from class field theory) and the discriminant, which in general have no meromorphic continuation to the entire complex plane.

Validation of Possible Applications of Flake Laminates for Recycling of PA6-CF Production Scrap - Beckmann, Johanna; Bachmann, Andre; Brandes, Philipp; Marten, Thorsten; Tröster, Thomas; Moritzer, Elmar (24th International Conference on Composite Materials (ICCM24))
Keywords: Faser-Kunststoff-Verbunde (FKV); Faserverstärkte Kunststoffe (FVK); Organobleche

„Und ich sag mal, Theorie und Praxis ist zweierlei“. Wie können Praxisphasen Lehramtsstudierende auf zukünftige Anforderungen vorbereiten? - Vernholz, Mats; Jonas-Ahrend, Gabriela; Temmen, Katrin (Zukünfte technischer Bildung)

Experimentelle und numerische Untersuchung des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Meschut, Gerson; Gilich, Julian; Gude, Maik; Koch, Ilja; Gröger, Benjamin; Wiebicke, Felix

Copper-supported thiol-functionalized cellulose as a paper-based catalyst for imine synthesis - Sangkaworn, Jariyaporn; Limprasart, Waranya; Höfler, Mark Valentin; Gutmann, Torsten; Pornsuwan, Soraya; Bunchuay, Thanthapatra; Tantirungrotechai, Jonggol (Scientific Reports)
This study presents an appealing approach to sustainable catalysis using cellulose filter paper as a support for copper-catalyzed reactions. The paper was functionalized with thiol groups through a reaction with thioglycolic acid, which served a dual purpose: partially reducing Cu(II) to Cu(I) and stabilizing active copper species via Cu–S interactions. Spectroscopic analysis confirmed the formation of highly dispersed multi-valent Cu2O/CuO on the thiol-functionalized cellulose, resulting in a highly efficient copper catalyst. This catalyst demonstrated excellent performance in the oxidative coupling of various amines to imines, achieving yields of 39–99% within 10–30 min. A key advantage of this system is its reusability; the catalyst maintained remarkable stability and activity over ten reaction cycles with straightforward recovery. This paper-based catalyst offers a promising strategy for eco-friendly and cost-effective synthetic processes, with significant implications for green chemistry and industrial applications.

Hyper-Cross-Linked Polyphosphines as Nanoporous Macroligands–A Systematic Study on Cross-Linking and Their Catalytic Application in the CO2 Hydrogenation - Nisters, Arne; Schleuning, Steffen; Buntkowsky, Gerd; Gutmann, Torsten; Rose, Marcus (ACS Applied Materials & Interfaces)
Hyper-cross-linked polymers (HCPs) enable the tailored synthesis of functionalized materials and provide a versatile design strategy for porous macroligands. Based on the prototypical triphenylphosphine (PPh3) monomer, we investigate the role of the involved cross-linking reagents in the formation of polyphosphines and evaluate structure–activity relations for application in the catalytic CO2 hydrogenation: namely by varying the Friedel–Crafts catalyst, the cross-linker unit and the degree of cross-linking. The study of monomeric reactivities shows that phosphines are insufficiently activated by iron chloride catalyzed cross-linking and that the stronger aluminum chloride is required to ensure PPh3 incorporation. Applying aromatic cross-linker units introduces porosity and promotes the accessibility of ligating centers for the immobilized ruthenium species. The thus formed solid catalysts exhibit excellent performances in the hydrogenation of CO2 to formic acid in the aqueous phase and are studied in successive recycling runs. The partial structural degradation of the frameworks during catalysis is addressed by adjusting higher degrees of cross-linking, leading to an improved stabilization of the catalyst. Overall, this study highlights cross-linking strategies for the tailoring of phosphine-based HCPs and the design of stable macroligands under catalytic conditions. Hyper-cross-linked polymers (HCPs) enable the tailored synthesis of functionalized materials and provide a versatile design strategy for porous macroligands. Based on the prototypical triphenylphosphine (PPh3) monomer, we investigate the role of the involved cross-linking reagents in the formation of polyphosphines and evaluate structure–activity relations for application in the catalytic CO2 hydrogenation: namely by varying the Friedel–Crafts catalyst, the cross-linker unit and the degree of cross-linking. The study of monomeric reactivities shows that phosphines are insufficiently activated by iron chloride catalyzed cross-linking and that the stronger aluminum chloride is required to ensure PPh3 incorporation. Applying aromatic cross-linker units introduces porosity and promotes the accessibility of ligating centers for the immobilized ruthenium species. The thus formed solid catalysts exhibit excellent performances in the hydrogenation of CO2 to formic acid in the aqueous phase and are studied in successive recycling runs. The partial structural degradation of the frameworks during catalysis is addressed by adjusting higher degrees of cross-linking, leading to an improved stabilization of the catalyst. Overall, this study highlights cross-linking strategies for the tailoring of phosphine-based HCPs and the design of stable macroligands under catalytic conditions.

Time resolved mobility changes of ionic liquids in cellulose by in-situ solid state NMR spectroscopy - Lins, Jonas; Pachernegg-Mair, Lukas; Höfler, Mark V.; Hajialilou, Solmaz; Spirk, Stefan; Gutmann, Torsten (Cellulose)
The understanding of the interactions between cellulose and ionic liquids are the foundation for the development of new processes, to explore new reactions and to establish a circular bioeconomy. The main problem is that direct measurement, from both quantitative and qualitative point of view is challenging. While there are methods to assess solution strength and wettability of ionic liquids with cellulose materials, the main challenge lies in the combination of a solid substrate and an applied liquid, limiting the number of accessible methods. We demonstrate in this paper that an in-situ solid-state NMR spectroscopical approach is capable of monitoring in real-time the mobility of ionic liquids in cellulose-based substrates. Specifically, we employ 1H → 13C cross polarization magic angle spinning (CP MAS) NMR spectroscopy to examine mobility changes over varying exposure times in paper samples treated with ionic liquids. Through this approach, we capture the temporal evolution of IL signals, which in turn provide insights into mobility changes of ILs and also allow for identifying changes in cellulose crystallinity. The approach allows for a simple, semiquantitative assessment of cellulose solubility in ionic liquids and is in principle applicable to other biomass materials as well.

Solid-state polycyclotrimerization of diynes to porous organic polymers - Hutsch, Stefanie; Grätz, Sven; Lins, Jonas; Gutmann, Torsten; Borchardt, Lars (Chemical Communications)
Herein, we report a solid-state polycyclotrimerization of 1,4-diethynylbenzene using mechanochemical activation in a ball mill, yielding a highly porous and hydrophobic hyperbranched polymer (HBP) with a specific surface area of up to 570 m2 g−1. The reaction, catalyzed by Fe(hmds)2 and conducted under solvent-free conditions, was optimized by varying milling time and frequency. This method enables the efficient synthesis of insoluble, porous organic polymers with high yields (up to 95%) and offers an environmentally friendly alternative to traditional solution-based polymerizations.

High-Sensitivity Gas-Phase Raman Spectroscopy for Time-Resolved In-Situ Analysis of Isotope Scrambling over Platinum Nanocatalysts - Koschnik, K.; Ferris, A. M.; Zhang, B.; Lill, J.; Stark, M.; Weinmann, A.; Limbach, H. H.; Gutmann, Torsten; Geyer, D.; Dreizler, A. (Analytical Chemistry)

Thermal Behavior of n-Octanol and Related Ether Alcohols - Hoffmann, Markus M.; Gutmann, Torsten; Buntkowsky, Gerd (Journal of Chemical & Engineering Data)
The thermal behavior of n-octanol and related ether alcohols has been studied by differential scanning calorimetry (DSC). The melting point, heat of fusion, and isobaric heat capacities of n-octanol obtained from the DSC measurements are in good agreement with literature values. The ether alcohols display kinetic barriers for forming a solid phase during cooldown. These barriers are least for 6-methoxyhexanol that forms a solid upon cooling except for the highest measured temperature change rate of 40 K·min–1, followed by 4-propoxybutanol that forms a solid during cooldown only at low cooling rates. 2-Pentoxyethanol and 5-ethoxypentanol form a solid during the heating cycle that then melts again upon further heating. 3-Butoxypropanol does not display any exo- and endothermic features for all measured temperature change rates. Consequently, new data on melting point and heats of fusion are reported for the ether alcohols except for 3-butoxypropanol. New isobaric heat capacities are presented as well for the liquid phase of these ether alcohols. The thermal behavior of n-octanol and related ether alcohols has been studied by differential scanning calorimetry (DSC). The melting point, heat of fusion, and isobaric heat capacities of n-octanol obtained from the DSC measurements are in good agreement with literature values. The ether alcohols display kinetic barriers for forming a solid phase during cooldown. These barriers are least for 6-methoxyhexanol that forms a solid upon cooling except for the highest measured temperature change rate of 40 K·min–1, followed by 4-propoxybutanol that forms a solid during cooldown only at low cooling rates. 2-Pentoxyethanol and 5-ethoxypentanol form a solid during the heating cycle that then melts again upon further heating. 3-Butoxypropanol does not display any exo- and endothermic features for all measured temperature change rates. Consequently, new data on melting point and heats of fusion are reported for the ether alcohols except for 3-butoxypropanol. New isobaric heat capacities are presented as well for the liquid phase of these ether alcohols.

Long-Term Cycling Stability of Sodium/Sodium Ion Cells Probed by In Situ Solid-State NMR Spectroscopy - Egert, Sonja; Remesh, Renuka; Jusdi, Agatha Clarissa; Sugawara, Yushi; Schutjajew, Konstantin; Oschatz, Martin; Buntkowsky, Gerd; Gutmann, Torsten (Batteries & Supercaps)
Sodium-ion batteries are at the forefront of new, sustainable energy systems required for the global energy transition. 23Na in situ solid-state nuclear magnetic resonance spectroscopy is capable of unraveling structures in working electrochemical cells during the charging and discharging processes. To evaluate its suitability for long-term studies, local sodium environments in sodium/sodium ion cells based on silicon carbonitride and hard carbon materials are tracked for up to 49 cycles (228.5?h). The formation of dendrites as well as the decay of a secondary metallic sodium species is observed, and local structures are analyzed up to the point of capacity degradation and cell failure. Initial points of cell breakdown are reflected in the NMR data by characteristic changes in signal intensities, whereas the degradation of the cells is reflected by a cease to periodic signal intensity fluctuations. Meanwhile, ex situ 23Na NMR spectra of the deactivated cells reveal a complex range of environments for sodium ions.
Keywords: solid-state nmr; hard carbon; in-situ; SiCN; sodium ion batteries

Highly active iron catalysts for olefin hydrogenation enable para-hydrogen induced hyperpolarisation of 1H and 19F NMR resonances at 1.4 Tesla - Doll, Julianna S.; Kergassner, Jan; Zhang, Bingyu; Thiele, Christina M.; Buntkowsky, Gerd; Enders, Markus; Gutmann, Torsten; Roşca, Dragoş-Adrian (Chemical Communications)
para-Hydrogen induced polarisation (PHIP) is an excellent tool for extracting mechanistic information in catalysis since it circumvents the intrinsic low sensitivity of nuclear magnetic resonance (NMR) spectroscopy. We report a class of iron complexes that are highly active in olefin hydrogenation catalysis and act as PHIP catalysts at 1.4 Tesla. Moreover, hyperpolarisation transfer to 19F is observed.

Monitoring chemical processes in redox flow batteries employing in situ and in operando analyses - Alem, Ahmad; Poormehrabi, Pooria; Lins, Jonas; Pachernegg-Mair, Lukas; Bandl, Christine; Ruiz, Virginia; Ventosa, Edgar; Spirk, Stefan; Gutmann, Torsten (Energy & Environmental Science)
Redox flow batteries (RFBs) are promising solutions for large-scale stationary energy storage due to their scalability and long cycle life. The efficient operation of RFBs requires a thorough understanding of the complex electrochemical processes occurring during charging and discharging. This review provides an overview and perspective of in situ and in operando analytical techniques to monitor RFBs. In more detail, these advanced techniques allow for real-time observation of redox reactions, ion transport, and electrode–electrolyte interactions under working conditions, offering insights into formation of intermediate species and mechanisms of electrolyte degradation, State-of-Charge (SoC), and ion crossover. By discussing the principles, capabilities, and limitations of techniques such as nuclear magnetic resonance (NMR), electron paramagnetic resonance (EPR), ultraviolet-visible (UV-vis) spectroscopy, Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray absorption spectroscopy (XAS), electrochemical impedance spectroscopy (EIS), tomography and radiography, mass spectrometry (MS), and fluorescence microscopy this review highlights the essential role of in situ and in operando approaches in advancing RFB technology.

Error estimates for full discretization of Cahn--Hilliard equation with dynamic boundary conditions - Bullerjahn, Nils; Kovács, Balázs (IMA Journal of Numerical Analysis)

Numerical analysis of an evolving bulk--surface model of tumour growth - Edelmann, Dominik; Kovács, Balázs; Lubich, Christian (IMA Journal of Numerical Analysis)

Maximal regularity of evolving FEMs for parabolic equations on an evolving surface - Bai, Genming; Kovács, Balázs; Li, Buyang (IMA Journal of Numerical Analysis)
In this paper, we prove that spatially semi-discrete evolving finite element method for parabolic equations on a given evolving hypersurface of arbitrary dimensions preserves the maximal $L^p$-regularity at the discrete level. We first establish the results on a stationary surface and then extend them, via a perturbation argument, to the case where the underlying surface is evolving under a prescribed velocity field. The proof combines techniques in evolving finite element method, properties of Green's functions on (discretised) closed surfaces, and local energy estimates for finite element methods

From Pixels to Words: Leveraging Explainability in Face Recognition Through Interactive Natural Language Processing - DeAndres-Tame, Ivan; Faisal, Muhammad; Tolosana, Ruben; Al-Refai, Rouqaiah; Vera-Rodriguez, Ruben; Terhörst, Philipp (Lecture Notes in Computer Science)

Effective Backdoor Learning on Open-Set Face Recognition Systems - Voth, Diana; Dane, Leonidas; Grebe, Jonas; Peitz, Sebastian; Terhörst, Philipp (2025 IEEE/CVF Winter Conference on Applications of Computer Vision (WACV))

FALCON: Fair Face Recognition via Local Optimal Feature Normalization - Al-Refai, Rouqaiah; Hempel, Philipp; Biagi, Clara; Terhörst, Philipp (2025 IEEE/CVF Winter Conference on Applications of Computer Vision (WACV))

BELIEF - Bayesian Sign Entropy Regularization for LIME Framework - Bora, Revoti Prasad; Terhörst, Philipp; Veldhuis, Raymond N. J.; Ramachandra, Raghavendra; Raja, Kiran Bylappa (Conference on Uncertainty in Artificial Intelligence, Rio Othon Palace, Rio de Janeiro, Brazil, 21-25 July 2025)